Lower female partner live birth rate in male cancer survivors: An age‐matched cohort analysis of the Utah Population Database. (3rd November 2021) - Patel, Darshan P.; Meeks, Huong T.; Pastuszak, Alexander W.; Hanson, Heidi A.; Smith, Ken R.; Letourneau, Joseph M.; Hotaling, James M.
Abstract: We determine the time to first live birth for female partners of males after a cancer diagnosis. Our group performed a retrospective, population‐based, age‐matched cohort study of Utah male residents diagnosed with cancer at age 18 years or later between 1956 and 2013 (exposed) matched to male Utah residents without cancer diagnosis (unexposed). Using stratified Cox proportional hazard models, we adjusted for race, ethnicity and number of live births prior to cancer diagnosis, to estimate the effect of time to a partner live birth following cancer diagnosis. Our study cohort included 19, 303 men diagnosed with cancer (exposed) and 93, 608 age‐matched men without cancer diagnoses (unexposed). Exposed men were less likely to have a live birth prior to first cancer diagnosis (60.7% vs. 65.4%, p < 0.001) and after first cancer diagnosis (10.9% vs. 12.2%, p < 0.001) compared to unexposed men. Exposed men had a fertility hazard rate that was 31% lower after cancer diagnosis date than unexposed men (HR: 0.69; 95% CI: 0.65–0.72). This was most profound for men aged 18–30 years (HR: 0.59, 95% CI: 0.55–0.63). Male cancer survivors have a 31% lower female partner live birth rate after cancer diagnosis. These findings are important for patient counselling regarding fertility preservation at the time of cancer diagnosis.